Performance Analysis and Optimal Portfolio Disversfication of Fifthteen Stocks of LQ-45 Index Period 2007 - 2012 Using Markowitz Modern Portfolio Theory - Paramitha, Fadila; Anggono, Achmad Herlanto (Journal of Business and Management, 2013)
The main theme of this research is Capital Market and focus on finding an Efficient and Optimal Portfolio based on the Markowitz Modern Portfolio Theory. Markowitz Modern Portfolio Theory explains that risk could be minimized by diverse the asset as a portfolio. It also explains than an optimal portfolio is a portfolio that gives highest return in a point of risk, or also meaning a portfolio with highest Sharpe ratio. Â To find an optimal portfolio, the author made a portfolio simulation. In that simulation, there were 25 portfolios that made from stocks which were established in Jakarta Composite Index. 14 stocks were chosen in the simulation, these stocks were a stock that listed in LQ-45 Index in the January 2nd 2007 up to January 2nd 2012 period. The author uses Solver Add-ins in the process of making the portfolio. From the portfolios that were made, the author compares the portfolios performance with the Jakarta Composite Index performance. The compartment includes risk, return, beta, Sharpe ratio, and Treynor ratio.Â The portfolio number 3 which had highest Sharpe ratio shows a better performance than the JCI, while had higher risk. The weight proportion of the Portfolio number 3 was 50.95% ASII, 33.42% BBCA, 9.06% PGAS, 3.98% BBRI and 2.59% PTBA. The result of the Sharpe ratio is 147.49%, the beta was 1.2 and the Treynor ratio is 60.31%. Expected return of this portfolio was 79.34% while giving 48.95% risk.Â Keywords: Stocks, LQ-45 Index, Risk and Return, Portfolio, Sharpe Ratio, Treynor Ratio, Solver, Efficient Frontier, Markowitz Modern Portfolio Theory